Sports Nutrition - Current Recommendations - Mosler S; Braun H; Carlsohn A; Großhauser M; König D; Lampen A; Nieß A; Oberritter H; Schäbethal K; Schek A; Stehle P; Virmani K; et al. (Deutsche Zeitschrift für Sportmedizin)
This position paper represents the current scientific recommendations for fluid management in sports. Sporting activities should always be commenced with a balanced fluid level (apparent by urine color, which is light yellow in the case of balanced fluid level).The loss of fluids during exercise depends on numerous factors such as the state of exercise, the intensity, duration, type of exercise and environmental factors. The weighing method to determine individual fluid loss offers guidance for the optimal fluid intake during exercise. In principle however, athletes should trust their own feeling of thirst.Generally in the case of activities lasting less than 30-40 minutes, fluid intake is not necessary, minor fluid deficits during exercise are tolerable. In the case of longer-lasting activity (>1.5 hours) it is advisable to take in beverages rich in carbohydrates and sodium. Therefore, the optimal sports drink should contain 400-1100 mg / l sodium in addition to carbohydrates (4-8%). After sport, fluids and electrolytes must be replaced. If there is no renewed physical activity in the next 24 hours and the body weight is reduced by less than 5%, consumption of normal meals and snacks in combination with an adequate supply of water is sufficient to restore fluid and electrolyte balance.For quick and complete rehydration, approximately 1.5 l of fluid per kg weight loss is recommended. KEY WORDS: Sports Drink, Fluid Intake, Fluid Balance, Electrolyte Balance